2017
DOI: 10.3390/ph10030060
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of β-Caryophyllene against Dopaminergic Neuron Injury in a Murine Model of Parkinson’s Disease Induced by MPTP

Abstract: Parkinson’s disease (PD) is one of the most common neurodegenerative disorders and is characterized by the loss of dopaminergic neurons in the substantia nigra (SN). Although the causes of PD are not understood, evidence suggests that its pathogenesis is associated with oxidative stress and inflammation. Recent studies have suggested a protective role of the cannabinoid signalling system in PD. β-caryophyllene (BCP) is a natural bicyclic sesquiterpene that is an agonist of the cannabinoid type 2 receptor (CB2R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 65 publications
2
65
0
Order By: Relevance
“…(a) inhibits H 2 O 2 , NO, TNF‐α, interferon gamma (IFN‐γ), and IL‐17 production; (b) reduces the number of inflammatory infiltrates; and (c) attenuates neurological damages in EAE‐mice (Fontes et al, ). In a similar fashion, Viveros‐Paredes et al () suggested that BCAR at 10 mg/kg (i.p.) exerts CB2 receptor‐mediated neuroprotection and inhibition of glia activation in mice.…”
Section: Neuropharmacological Effects Of β‐Caryophyllenementioning
confidence: 77%
“…(a) inhibits H 2 O 2 , NO, TNF‐α, interferon gamma (IFN‐γ), and IL‐17 production; (b) reduces the number of inflammatory infiltrates; and (c) attenuates neurological damages in EAE‐mice (Fontes et al, ). In a similar fashion, Viveros‐Paredes et al () suggested that BCAR at 10 mg/kg (i.p.) exerts CB2 receptor‐mediated neuroprotection and inhibition of glia activation in mice.…”
Section: Neuropharmacological Effects Of β‐Caryophyllenementioning
confidence: 77%
“…All these effects are related to CB2/Nrf2 pathway [29]. Research on a mouse model of Parkinson's disease conducted by Viveros-Paredes revealed that the treatment with BCP, at the dose of 10 mg/kg, enhances motor coordination in mice and protects the dopaminergic neurons from degeneration, reducing the production of inflammatory cytokines, in particular IL-1β, IL-6, and TNF-α [30].…”
Section: β-Caryophyllene and Nervous Systemmentioning
confidence: 99%
“…It acts as an agonist of cannabinoid CB2 and PPAR (peroxisome proliferator activated receptor) receptors, thus leading to beneficial effects on several diseases, such as neuroinflammation, neurodegenerative pathologies and some types of cancer [37]. Furthermore, it produces cytoprotective effects by modulating oxidative stress, apoptosis and inflammation [38][39][40][41], through the interference with different inflammatory pathways, such as the inducible nitric oxide synthase (iNOS), tumor necrosis factor-alfa (TNF-α) and nuclear factor-κB (NF-κB) [37]. Also, it exhibited chemopreventive properties, such as genoprotective and antiproliferative ones, by inhibiting DNA damage and STAT3 (signal transducer and activator of transcription 3) activation induced by environmental pollutants [31,32,42,43] and through affecting multiple cascades involved in cancer growth [37,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous evidence about the chemosensitizing properties of caryophyllane sesquiterpenes [24][25][26]50], in the present study we evaluated the ability of β-caryophyllene to synergize doxorubicin ( Figure 1) in Mz-ChA-1 cholangiocarcinoma cells under both long-term and metronomic exposure schedules. Furthermore, being β-caryophyllene known to be protective in normal tissue against several toxicants [31,32,[38][39][40][41][42][43], its ability to reduce doxorubicin toxicity in H69 noncancerous cholangiocytes, under the same exposure schedules applied for the doxorubicin chemosensitization, was assessed too. This could represent an important goal to overcome the toxicity drawback of doxorubicin chemotherapy while maintaining its anticancer efficacy.…”
Section: Introductionmentioning
confidence: 99%